Nanotechnologies and membrane engineering at the core of water and related questions in the Mediterranean and Middle-East countries - Rios G.M. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
After a short recall on the importance of water questions for Mediterranean countries, membranes are presented as breakthrough technologies for the field of desalination. Then basic recalls are done concerning membrane materials and processes. A few examples of new very promising materials and processes operating at the nanoscale, not only for desalination but also with other water treatment applications, are presented. As a conclusion, a few ideas are proposed about the best ways to approach all these questions in the future. Undoubtedly, with cell membranes as an ultimate model, all these breakthrough bio-mimetic approaches offer a privileged direction to reach sustainable development.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)